Hegemon wbrew własnej woli? Problemy i wyzwania dla przywództwa Niemiec w Unii Europejskiej w drugiej dekadzie XXI wieku - Koszel, Bogdan (Rocznik Integracji Europejskiej, 2015)
In the paper the author analyses the main issues related to the leadership of Germany in the EU in the 2010s. Among them are the financial crisis in the euro zone, the weakening of the Franco-German engine of European integration, the crisis in Ukraine and the prospects for Grexit and Brexit. He indicates that the Germans, although quite reluctantly, are taking advan- tage of an economic situation which is favourable for them and have taken the position of un- questionable leader in the European Union.